Emotional arousal and valence in patients with fibromyalgia: a pilot study - Ciuffini, Roberta; Cofini, Vincenza; Muselli, Mario; Necozione, Stefano; Piroli, Alba; Marrelli, Alfonso (Frontiers in Pain Research, 2023)
The pathogenesis of pain in fibromyalgia is still not completely understood. A disrupted emotional modulation could affect the physiology of nociception and contributes to an altered perception of pain. The aim of this study was to test the role of emotional arousal and valence in pain susceptibility in fibromyalgia using the International Affective Picture System (IAPS) paradigm and the Fibromyalgia Severity Scale (FSS). The study focused on comparing emotional arousal and valence between patients with fibromyalgia and the control group. The secondary objective was to examine the correlation between emotional indices and scores on the FSS and the duration of the disease. The 20 patients with fibromyalgia enrolled showed a higher mean arousal score for all the stimuli, including a higher score for unpleasant and socially unpleasant stimuli. The valence scores for social-relevant stimuli were also higher. Increased arousal to unpleasant and socially unpleasant images and increased valence of them correlated with the duration of the disease and the severity of symptoms and could reflect impairment in social cognition and marked sensitivity to pain in interaction with central nociceptive dysregulation.